Pelatihan Penggunaan Aplikasi Mobile Pertanian Untuk Pelaku Usaha Tani Di Desa Panyocokan - Asep Somantri; Rita Rijayanti (Jurnal Pengabdian Pada Masyarakat, 2022)
TRAINING ON THE USE OF AGRICULTURAL MOBILE APPLICATIONS FOR FARMERS IN PANYOCOKAN VILLAGE. The prospect of using smartphones is increasingly expanding, including for agricultural businesses. This study shows how important it is to carry out skills training for agricultural business actors in using smartphones that are directed at the use of special applications to support agricultural businesses. This needs to be done as an effort to support the improvement of skills and knowledge in agriculture in Panyocokan Village, Ciwidey District, Bandung Regency. The target participants in this activity are farmers, extension workers, and agricultural business actors who have difficulty in obtaining the information they need about agriculture. Information that will be provided in the application includes varieties, cultivation methods, fertilization, plant-disturbing organisms, pesticides, pest control, pesticide spraying, post-harvest, crop price information, and consultation with experts. The training method is carried out by online learning which begins with data collection, situation analysis on the potential of the agricultural and plantation sectors, preparation of training scenarios, training implementation, and evaluation of training results. This research resulted in an increase in skills in using smartphones to support agricultural businesses with the support of training materials and application manuals.